Oxygen-related defects and luminescence properties of CaMoO4 single crystals and CaMoO4-CaWO4 compounds - Zakharko, Ya.; Luchechko, A.; Solskii, I. (Видавництво Львівської політехніки, 2012)
Emission spectra under UV and X-ray excitations, as well as luminescence decay kinetics of CaMoO4 single crystals and CaMoO4-CaWO4 mixed structures were studied. The broad luminescence bands with maxima at 425 and 530 nm correspond to CaWO4 and CaMoO4 crystals, respectively. The decay kinetics show nonsingle exponential behavior for all investigated CaMoO4- CaWO4 samples at room temperature.
Keywords: CaMoO4; solid solutions; photo- and X-ray luminescence; decay time